Pengembangan Media Interaktif Tata Surya Pada Pembelajaran Untuk Meningkatkan Hasil Belajar IPA Kelas VI SDN 1 Gunung Terang - Elvadola, Connyta; Juwantara, Ridho Agung; Kurniasih, Try Indiastuti; Rasitiani, Amilia (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2023)
The purpose of this study was to determine the effectiveness of developing interactive media on solar system material in improving student learning outcomes. The method used is the Research and Development method (research and development). The stages of development in this study began with analyzing needs, designing, making interactive media, then applying it in learning and then testing student learning outcomes. Data analysis was carried out using descriptive percentages and one sample test for student completeness. This can be seen from the validation results of material experts who stated "very feasible", while media experts for the media aspect were declared "very feasible", and for the language aspect it was declared "very feasible". Whereas for the student response questionnaire it was declared "very interesting" and for the educator's response questionnaire it was stated "very interesting". The developed media can also improve student learning outcomes by obtaining a percentage of 92.30% with very good qualifications.